Knowledge and practice involving disaster management - Zainuddin, Nizamuddin; A. Rahman, Badruddin; Deraman, Norita (2010)
This paperwork highlighted a study done on the preparedness of the human resource involve under several agencies in Kedah on the level of understanding (knowledge) and practice of Directive No.20.Directive No.20 is about the Policy and Mechanism on National.Disaster Management and Relief.The main purpose of the directive is to create systematic coordination among agencies involve in disaster management as well as relief and rehabilitation. It has been issued by the National Security Division (NSD) of the Prime Minister Department in 1997.A total of 15 agencies covering 9 districts made up the population of the study in which 120 respondents were selected based on proportionate stratified sampling.The response rate was 40% and the findings did confirm the relationships (positive correlation) between understanding the knowledge of Directive No. 20 and the practice of Directive No.20.Multiple Regression had also been used to ascertain whether the knowledge and practice of Directives No. 20 contribute to disaster preparedness factors.The test confirmed that both the independent variables explained 86 per cent (R2= 0.860) of the variance in disaster preparedness, which is highly significant as indicated by the F-value (F = 137.651, p < 0.05).